THE EFFECT OF GIVING DIFFERENT NATURAL FEEDS TO THE GROWTH OF BLACK GHOST FISH LARVAE(Apteronotus albifrons) - Sri Faulina Nainggolan; Nuraini Nuraini; Sukendi Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abtrac This research was conducted from September to November 2018 in the fish breeding and breeding laboratory (PPI) Department of Aquaculture, Faculty of Fisheries and Marine, University of Riau, Pekanbaru. The purpose of this study was to determine the effect of different natural feeds and the best natural feed on the growth and survival of black ghost fish larvae (Apteronotus albifrons). The method used in this study is the experimental method that uses one-factor Completely Randomized Design (CRD) consisting of four treatments with three replications. The treatment applied in this study is P1: Feeding Artemia sp. (40 days) P2: Feeding Water Lice (40 days), P3: Feeding Tubifex sp (40 days), P4: Feeding Earthworms (40 days). The results showed that the best treatment of different natural foods was found in Tubifex sp. Maintenance of black ghost fish larvae produces absolute weight growth values of 0.73 grams, growth of absolute length of 3.71 cm, specific growth rate of 13.28% and livelihood of 91.00%. Water quality during the study was temperature ranging from 26.2 - 28.50C, pH ranged from 6.9-7.7 and DO was 5.2-6.3 Keywords : Natural Feed, Artemia sp, Water Lice, Tubifex sp., Earthworm, Larvae of black ghost fish (Apteronotus albifrons)